DNaseI sensitivity of the rat albumin and alpha-fetoprotein genes. - Kunnath, L (1985)
We have analyzed the DNaseI sensitivity of chromatin from the rat albumin and alpha-fetoprotein genes in the fetal liver (which synthesizes albumin and alpha-fetoprotein), adult liver (which synthesizes albumin), fetal yolk sac (which synthesizes alpha-fetoprotein), and adult kidney (which synthesizes neither). Active genes were much more sensitive than their kidney counterparts, and the adult liver alpha-fetoprotein and fetal yolk sac albumin genes showed intermediate levels of sensitivity. Sensitivity was analyzed as a function of the extent of DNaseI digestion. Rate constants were calculated for the degradation of individual DNA hybridization bands and normalized to the intrinsic rate constants of the same bands degraded in purified DNA. This enabled us to eliminate the inconsistencies that otherwise result from comparing chromatin sensitivity of different DNA sequences, or chromatin sensitivity in different nuclear environments.